A case report: New-onset refractory status epilepticus in a patient with FASTKD2-related mitochondrial disease - Astner-Rohracher, Alexandra; Mauritz, Matthias; Leitinger, Markus; Rossini, Fabio; Kalss, Gudrun; Neuray, Caroline; Retter, Elisabeth; Wortmann, Saskia B.; Achleitner, Melanie T.; Mayr, Johannes A.; Trinka, Eugen (Frontiers in Neurology, 2023)
Introduction: New onset refractory status epilepticus (NORSE) is associated with high morbidity and mortality. Despite extensive work-up, the underlying etiology remains unknown in 50% of affected individuals. Mitochondrial disorders represent rare causes of NORSE. Biallelic variants in FASTKD2 were reported as cause of infantile encephalomyopathy with refractory epilepsy. Case Description: Here we report a previously healthy 14-year-old with a new, homozygous FASTKD2 variant, presenting with NORSE. Following a seizure free period of 7 years, he experienced another super-refractory SE and subsequently developed drug resistant focal epilepsy, mild myopathy, optic atrophy and discrete psychomotor slowing. Structural MRI at the time of NORSE showed right temporo-parieto-occipital FLAIR hyperintensity and diffusion restriction, with extensive right hemispheric atrophy at the age of 22 years. Whole exome sequencing revealed a novel homozygous loss of function variant (c.[1072C>T];[1072C>T] (p.[Arg358Ter];[Arg358Ter]) in FASTKD2 (NM_001136193), resulting in a premature termination codon in the protein coding region and loss of function of FASTKD2. Oxidative phosphorylation (OXPHOS) in muscle and skin fibroblasts was unremarkable. Conclusion: This is the first case of a normally developed adolescent with a new homozygous loss of function variant in FASTKD2, manifesting with NORSE. The phenotypical spectrum of FASTKD2 related mitochondrial disease is heterogeneous, ranging from recurrent status epilepticus and refractory focal epilepsy in an adolescent with normal cognitive development to severe forms of an infantile mitochondrial encephalopathy. Although mitochondrial diseases are rare causes of NORSE, clinical features like young age at onset and multi-system involvement should trigger genetic testing. Early diagnosis is essential for counselling and treatment considerations.